Urban Green Space Usage and Nature Satisfaction Across Life Course Phases and Socio-Economic Class. - Dovbischuk, Tetiana (New York, USA Routledge, 2025)
This book provides an analysis of nature satisfaction, nature relatedness, and the motivations for using urban green spaces. It explores the use of spaces such as parks, waterfronts, wooded areas, and fields among different life course phases and socio-economic classes. Through a detailed analysis of primary data from two major German cities, Cologne and Hamburg, the book examines the availability, use, and satisfaction with urban green spaces and provides insights into the predictors of nature satisfaction in an urban context. The book also combines the subjective assessments of the respondents with objective data. It considers the varying reliance on urban green spaces due to the availability of private green spaces and individual nature relatedness. It provides insights on the needs of different population groups in cities, providing a scientific basis for improving or implementing green space planning approaches. This book will be of interest to researchers in sociology, urban studies, public health, environmental studies, and human geography.
Keywords: Open spaces -- Social aspects; Urban ecology (Sociology); SOCIAL SCIENCE / Human Geography